Jonson and Shakespeare: Oedipal Revenge. Issue 1 (May 2016) - Dutton, Richard
Abstract : Jonson's attacks on Shakespeare's popular stagecraft, in the Induction to Bartholomew Fair and the Prologue to the folio version of Every Man In His Humour, are both well known. This essay argues that the focus of these attacks extends to an area of the dramatists' rivalry that has not hitherto been explored, in the presentation of their plays at court. While it is known that Shakespeare's plays were frequently performed at court the evidence for the presentation of Jonson's plays there is more patchy. But the essay marshals it to suggest that the sequence of plays collected in the 1616 Works is in part a proud record of their performance at court, where he was now poet laureate in all but title, while the Prologue to Every Man In implicitly questions the fitness of Shakespeare's plays for presentation there. Such questioning extends into Bartholomew Fair itself, whose presentation at court on the first day of the 1614/15 Revels season has all the appearance of a command performance. Winwife's choice of the word "Palemon" ("out of the play"), in the lottery to win Grace Wellborn, inevitably evokes The Two Noble Kinsmen and its reworking of Chaucer's "The Knight's Tale, " as does the puppet-show's depiction of feuding former friends (though Littlewit has ludicrously confused Palemon and Arcite with Damon and Pythias). That confusion, however, redirects us to the early Elizabethan court plays by Richard Edwardes on these two pairs of friends, models of courtly tragicomedy with which Shakespeare and Fletcher's latest offering compares poorly.